2019
DOI: 10.1016/j.autrev.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles in autoimmune vasculitis - Little dirts light the fire in blood vessels

Abstract: Systemic vasculitis is diverse group of autoimmune disorders which are characterized by inflammation of blood vessel walls with deep aching and burning pain. Their underlying etiology and pathophysiology still remain poorly understood. Extracellular vesicles (EVs), including exosomes, microvesicles (MVs), and apoptotic bodies, are membrane vesicular structures that are released either during cell activation, or when cells undergo programmed cell death, including apoptosis, necroptosis, and pyroptosis. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 197 publications
2
50
0
2
Order By: Relevance
“…Phosphotidylserine is a marker of EV generation 34 . The sizes of these membrane surface domains are consistent with the recognized size range for membrane microvesicles (approximately 0.1 to 1 µm) 26,27,35 . Thus, A23187 treatment appears to induce the budding and release of EV-associated TOP protein.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Phosphotidylserine is a marker of EV generation 34 . The sizes of these membrane surface domains are consistent with the recognized size range for membrane microvesicles (approximately 0.1 to 1 µm) 26,27,35 . Thus, A23187 treatment appears to induce the budding and release of EV-associated TOP protein.…”
Section: Resultssupporting
confidence: 80%
“…Extracellular vesicles (EVs) are small cellular membrane vesicles that are either released from intracellular space (exosomes) 27 , or budded from the plasma membrane surface of almost all cell types upon cell activation or programmed cell death (microvesicles) [23][24][25][26][27] . In the past several years, the biomedical research field has shown growing interest in the biological roles of EVs due to their emerging roles in pathophysiological conditions and various human diseases 26,27 . Studies show that EVs carry a heterogeneous array of intracellular and membrane-associated biologically active molecules, such as proteins, lipids, and DNA or RNA [23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs were defined in 1967 as "dust" from platelets (130). More recently, it has been shown that EVs are membrane vesicles that are released by almost all eukaryotic cells during cell activation and programmed cell death (131)(132)(133)(134). Heterogeneity of EVs is essential.…”
Section: Extracellular Vesicles In Primary Systemic Vasculitidesmentioning
confidence: 99%
“…Heterogeneity of EVs is essential. They are classified into three groups with regard to biological features and their size: exosomes, microvesicles (MVs), and apoptotic bodies (132,133,135,136). EVs are responsible for immune regulation, cell-to-cell interaction, and signal transmission by transporting bioactive molecules including proteins and lipids, DNA, and various RNAs, such as mRNAs, small-interfering RNAs (siRNAs), microRNAs (miRNAs), and long non-coding RNAs (lncRNAs) and other molecules produced by cells (132,(137)(138)(139).…”
Section: Extracellular Vesicles In Primary Systemic Vasculitidesmentioning
confidence: 99%